MINERALOGICAL ANALYSIS OF ROCK WEATHERING AND ITS INFLUENCE ON SLOPE FAILURE ALONG THE JAYAPURA CITY RING ROAD - Karapa, Enos; Joni, Joni; Hartiningsih, Endang; Yonas, Marcelino Novryanto; Indrajati, Rahmat; Patabang, Djuarensi; Anas, Nur Ayu (LPPM Universitas Jambi, 2026)
Slope failure along the Jayapura City Ring Road persisted despite shotcrete reinforcement, indicating that instability is not controlled solely by slope geometry or surface confinement. Field evidence points to weakening within foliated metamorphic rocks affected by tropical weathering, where mineral alteration progressively modifies the internal structure. This study examines how mineralogical transformations govern subsurface degradation and contribute to failure beneath reinforced slopes. A case study approach was applied using two representative samples (ST-01 and ST-02) obtained directly from the failure zone. Petrographic analysis of 30 μm thin sections was conducted to evaluate mineral textures, fabric orientation, and alteration pathways. X-ray diffraction (XRD) was used to identify and semi-quantify the mineral phases, including albite, quartz, chlorite, muscovite, sericite, and magnetite. Subsurface conditions were assessed using ADMT resistivity profiling across a frequency range of 0.0001–10,000 Hz, reaching depths of approximately 300 m. The results indicate a mineralogical transition from a wollastonite–actinolite–chlorite assemblage in ST-01 to a chlorite–muscovite–sericite-dominated system in ST-02. The XRD data show a decrease in albite from 19.74% to 11.61%, while an unresolved fraction exceeding 20% suggests the presence of poorly crystalline phases. Petrographic observations revealed that chlorite and sericite were concentrated along foliation and microfractures. The resistivity data identified a low-resistivity zone (10–20 Ωm) at depths of 10–60 m, corresponding to altered and fluid-influenced domains. These findings indicate that weathering reduces cohesion along structurally controlled planes while preserving partial framework integrity, shifting the locus of failure to the subsurface beneath the shotcrete layer.